Ancient and Archaic Genomes - Caramelli, David; Lari, Martina; Vai, Stefania (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The development of high-throughput sequencing has triggered a revolution in the study of ancient DNA. In the last decade, methodological advances have allowed researchers to overcome some of the limits linked to the degradation and preservation of nucleic acids, improving the capacity of recovery and analysis of the ancient molecules. This fact, along with a wider accessibility to the next-generation sequencing platforms, has contributed to increase the number of genomic studies on ancient remains. This Special Issue, titled "Ancient and Archaic Genomes", collects original research articles that present different methods and aspects of the paleogenetic research applied to anthropological, archaeological, and historic questions. Interestingly, specific regional contexts and cultural aspects previously poorly studied from a genetic point of view are here investigated. This Special Issue, presenting different methodological approaches and applications, will be a useful resource for both students and young researchers who are interested in ancient DNA studies.